The Influence of Dividend Policy, Capital Structure and Institutional Ownership Structure on Agency Costs (in Consumer Goods Sector Manufacturing Companies listed on the Indonesian Stock Exchange for the 2019-2022 Period) - Wachidah, Durrotul; Hazmi, Shadrina (Journal of Finance and Business Digital, 2024)
This research was conducted to analyze the influence of dividend policy, capital structure and institutional ownership structure on agency costs in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2019 - 2022. The sample used was 57 companies. The data obtained was collected using purposive sampling techniques in annual financial reports so that 14 companies were found in accordance with predetermined requirements. The results of this research prove that: (1) dividend policy has a significant positive effect on agency costs, (2) capital structure has a significant negative effect on agency costs, (3) institutional ownership structure has a positive and significant effect on agency costs, (4) dividend policy, capital structure and institutional ownership structure have a significant positive effect on agency costs.